Hubungan Nyeri dengan Delirium pada Pasien yang Terintubasi di ICU RSUP Haji Adam Malik Medan - Nurchotijah, Nurchotijah; Lubis, Andriamuri Primaputra; Hamdi, Tasrif (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
Introduction: Pain can sometimes trigger a stress response and stimulate adrenergic-sympathetic activity. Delirium, a serious disruption of consciousness, is characterized by fluctuating perceptions, confused thinking, and varying levels of attention. Undiagnosed pain and delirium can lead to increased infection rates, prolonged mechanical ventilation, hemodynamic instability, and delirium. This study utilizes the Critical-Care Pain Observation Tool (CPOT) to measure pain and the Confusion Assessment Method (CAM) ICU to evaluate delirium in intubated patients in the ICU of RSUP HAM to explore the connection between pain and delirium. Method: The research employed a quantitative, cross-sectional observational analytical method. It investigated the association between pain and delirium in patients who were intubated at H. Adam Malik General Hospital Medan between January and February 2023, using the CPOT and CAM ICU scales. The chi-square test was used to analyze the relationship between pain and delirium, as well as the relationship between confounding factors and both pain and delirium. Results: The association between pain and delirium had a P-value of 0.001. The association between fentanyl dosage and pain in intubated patients also had a P-value of 0.001. Confounding factors included the length of stay with pain (P-value less than 0.001) and delirium with age (P-value = 0.026), gender (P-value = 0.013), and length of stay (P-value = 0.001). However, the doses of fentanyl and midazolam showed no significant association between patients with and without delirium (P-value = 0.5). Conclusion: There is a significant associations between pain and delirium.